Theological Frames for Social Research - Smith, Michael (Journal of empirical theology, 2018)
In this article, theological frames are introduced as a qualitative tool for empirical theological research on Christian organisations. Theological frames are defined as frameworks for the theological interpretation of social life and are offered to further comparative and explanatory research on lived religion. Theological frames are developed by integrating frame theory (Bateson 1972; Goffman 2974; Snow et al. 1986) with the four voices of theology Bhatti et al. (2010) to understand the effects of nuanced theological expressions on social life. A methodology for constructing theological frames in social research is given, then applied to a socially engaged Australian Christian advocacy organisation.